2010
DOI: 10.1089/ten.teb.2009.0590
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Articular Cartilage Lesion Repair and Functional Restoration

Abstract: Injury of articular cartilage due to trauma or pathological conditions is the major cause of disability worldwide, especially in North America. The increasing number of patients suffering from joint-related conditions leads to a concomitant increase in the economic burden. In this review article, we focus on strategies to repair and replace knee joint cartilage, since knee-associated disabilities are more prevalent than any other joint. Because of inadequacies associated with widely used approaches, the orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
233
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(237 citation statements)
references
References 248 publications
2
233
0
2
Order By: Relevance
“…Different techniques are used to injury subchondral bone, such as abrasion chondroplasty, Pridie drilling, spongialization and microfracture (6)(7)(8), producing bleeding in the zone of osteoarthritic lesion and clot formation, that initiate bone marrow stem cells migration and thus the regenerative process. These techniques take the advantage of the body's own healing potential (8), representing an easy, simple, minimally invasive, low-morbidity, single-stage procedure, and it has been reported to be cost-effective, associated with few complications, with a high capacity for creation of durable repair tissue, and with best long-term results in younger active patients with isolated small lesions (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different techniques are used to injury subchondral bone, such as abrasion chondroplasty, Pridie drilling, spongialization and microfracture (6)(7)(8), producing bleeding in the zone of osteoarthritic lesion and clot formation, that initiate bone marrow stem cells migration and thus the regenerative process. These techniques take the advantage of the body's own healing potential (8), representing an easy, simple, minimally invasive, low-morbidity, single-stage procedure, and it has been reported to be cost-effective, associated with few complications, with a high capacity for creation of durable repair tissue, and with best long-term results in younger active patients with isolated small lesions (13).…”
Section: Discussionmentioning
confidence: 99%
“…Scaffolds rapidly fill cartilage defects and provide a temporary substrate onto which invading cells can adhere. They also play important roles in maintaining mechanical integrity and withstanding mechanical stresses, therefore they should be designed to match mechanical properties with those of native cartilage, as well as appropriate for the loading conditions of the joint (6,15,16). Different "in vivo" studies had demonstrated the importance of the stress transmission to the cells in cartilage regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…40 The DeNovo ET Engineered Tissue Graft (Zimmer, Inc) and Cartilage Autograft Implantation System (CAIS; DePuy Mitek, Inc, Raynham, MA) are alternative techniques currently under investigation. The DeNovo ET uses juvenile allogenic chondrocytes in culture to create a 3-dimensional sheet of cartilage, 2 while CAIS uses autogenic donor tissue that is procured from a non-weight-bearing region, minced, and implanted to the defect site on a scaffold placed into the defect. Both technologies are still under investigation and are about to undergo phase III clinical trial enrollment.…”
Section: Emerging Future Techniquesmentioning
confidence: 99%
“…Such orientation is essential in properly executing a number of chondral resurfacing and restorative techniques, namely microfracture, mosaicplasty, and autologous matrixinduced chondrogenesis. 3,7,11,23,26,31 Thus, the findings of the present study are valuable in providing the arthroscopist with an alternative portal option that may allow him or her to address deep, centralized chondral lesions of the patella effectively while maintaining an arthroscopic approach.…”
Section: Resultsmentioning
confidence: 86%